5(z+6)-2=9forz

Simple and best practice solution for 5(z+6)-2=9forz equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(z+6)-2=9forz equation:


Simplifying
5(z + 6) + -2 = 9forz

Reorder the terms:
5(6 + z) + -2 = 9forz
(6 * 5 + z * 5) + -2 = 9forz
(30 + 5z) + -2 = 9forz

Reorder the terms:
30 + -2 + 5z = 9forz

Combine like terms: 30 + -2 = 28
28 + 5z = 9forz

Solving
28 + 5z = 9forz

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9forz' to each side of the equation.
28 + -9forz + 5z = 9forz + -9forz

Combine like terms: 9forz + -9forz = 0
28 + -9forz + 5z = 0

Add '-28' to each side of the equation.
28 + -9forz + -28 + 5z = 0 + -28

Reorder the terms:
28 + -28 + -9forz + 5z = 0 + -28

Combine like terms: 28 + -28 = 0
0 + -9forz + 5z = 0 + -28
-9forz + 5z = 0 + -28

Combine like terms: 0 + -28 = -28
-9forz + 5z = -28

Reorder the terms:
28 + -9forz + 5z = -28 + 28

Combine like terms: -28 + 28 = 0
28 + -9forz + 5z = 0

The solution to this equation could not be determined.

See similar equations:

| tan^-1(8/13) | | 5(y+1)=3 | | Abs(-7a)=28 | | sin(40)=8/x | | sin40=8/x | | F(x)=-4x^2+16 | | 6W+193=55 | | x+12=m+32 | | 8x-6x+25=35 | | 6(t-4)=3t+3 | | 8-6x+25=35 | | N^2+9n+9=0 | | 3(p+4)=2p-7 | | 5x+89=29 | | 2u+91=27 | | -7+0.25m=7 | | 0.8x+23=-25 | | 2x+24=18 | | 0.8x+23=25 | | -16a+67=3 | | 7x-35-3x=2x-13 | | 2x+24=78 | | 5c+17=2 | | -7v+81=32 | | -7v+81=7 | | 9b+50=275 | | 5y-10=-35 | | 25+11.12b=47 | | -2h+7=45 | | 6(4x-6)+18=6 | | 3s+158=-16 | | 8(x-4)-18=22 |

Equations solver categories